Himpunan Penyelesaian dari
-x+y+z=7
3x-2y-z=-8
2x+3y-z=6
Jawaban:
x = 3
y = 5
z = 5
Penjelasan dengan langkah-langkah:
-x+y+z = 7 (1)
3x-2y-z = -8 (2)
2x+3y-z = 6 (3)
dari pers 2&3 eliminasi x
3x-2y-z = -8 (×2)
2x+3y-z = 6 (×3)
maka
6x-4y-2z = -16
6x+9y-3z = 18
———————— –
-13y+z = 34 (4)
dari pers 1&3 eliminasi x
-x+y+z = 7 (×2)
2x+3y-z = 6 (×1)
maka
-2x+2y+2z = 14
2x+3y-z = 6
————————— +
5y-z = 20 (5)
dari pers 4&5 eliminasi z
-13y+z =20
5y-z = 20
——————— +
8y =40
y = 5
dari pers 5
5y-z = 20
5×5-z = 20
25-z = 20
-z = 20-25
-z = -5
z = 5
dari pers 1
-x+y+z=7
-x+5+5 = 7
-x = 7-10
-x = -3
x = 3